Interstitial Fluid in Gynecologic Tumors and Its Possible Application in the Clinical Practice. - Ura, Blendi; Di Lorenzo, Giovanni; Romano, Federico; Monasta, Lorenzo; Mirenda, Giuseppe; Scrimin, Federica; Ricci, Giuseppe (Int J Mol Sci, 2018)
Gynecologic cancers are an important cause of worldwide mortality. The interstitium consists of solid and fluid phases, situated between the blood vessels and cells. The interstitial fluid (IF), or fluid phase, is an extracellular fluid bathing and surrounding the tissue cells. The TIF (tumor interstitial fluid) is a dynamic fluid rich in lipids, proteins and enzyme-derived substances. The molecules found in the IF may be associated with pathological changes in tissues leading to cancer growth and metastatization. Proteomic techniques have allowed an extensive study of the composition of the TIF as a source of biomarkers for gynecologic cancers. In our review, we analyze the composition of the TIF, its formation process, the sampling methods, the consequences of its accumulation and the proteomic analyses performed, that make TIF valuable for monitoring different types of cancers.
Keywords: Biomarkers, Tumor; Biophysical Phenomena; Extracellular Fluid; Female; Genital Neoplasms, Female; Humans; Practice Patterns, Physicians'; Tumor Microenvironment